Nursing consultation for people with diabetes mellitus: experience with an active methodology - Silvana de Oliveira Silva; Letícia Martins Machado; Maria Denise Schimith; Laís Mara Caetano da Silva; Vanessa do Nascimento Silveira; Anderson Cecchin de Bastos
ABSTRACT Objective: to describe our experience with a methodology for teaching nursing consultation in support of people with diabetes mellitus at a Family Health Unit. Method: experience report with four moments-submission of the proposal to the team; theorizing; nursing care for people with diabetes mellitus at home and at the health unit, and evaluation of learning. Results: the pedagogical process favored the integration between service and users, contributed to implement and apply the nursing process and strengthened professional training, based on the epidemiological profile of chronic diseases and its implications for nursing in primary care. Final considerations: the active methodology discussed here allowed for a resignification of knowledge and a qualification of nursing care, demonstrating to be an important instrument for integrating clinical practice and epidemiology in accordance to experienced reality.